2008
DOI: 10.1167/iovs.07-0385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progressive Addition Lenses on Myopia Progression in Japanese Children: A Prospective, Randomized, Double-Masked, Crossover Trial

Abstract: The use of PALs slowed myopia progression, although the treatment effect was small, as previously reported in ethnically diverse children in the United States. The significant treatment-by-period interaction suggests that early application of PALs would probably be more beneficial for these age and refraction ranges (isrctn.org number, 28611140).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 47 publications
2
110
0
2
Order By: Relevance
“…The value of using this selection criterion to identify children with high myopic progression is confirmed: the 24-month rate of myopic progression of −1.55 D in the single-vision lens group (control group) is greater than those of previous myopiacontrol studies. [8][9][10][11][12][13] Our study supports the findings of Leung and Brown, 9 who used a similar inclusion criterion; progressive lenses are effective at inhibiting myopic progression for myopic children with high myopic progression.…”
Section: Commentsupporting
confidence: 81%
“…The value of using this selection criterion to identify children with high myopic progression is confirmed: the 24-month rate of myopic progression of −1.55 D in the single-vision lens group (control group) is greater than those of previous myopiacontrol studies. [8][9][10][11][12][13] Our study supports the findings of Leung and Brown, 9 who used a similar inclusion criterion; progressive lenses are effective at inhibiting myopic progression for myopic children with high myopic progression.…”
Section: Commentsupporting
confidence: 81%
“…Similarly, bifocal spectacles have been reported to prevent progression of mild or moderate myopia. 42,43 These studies showed an overall adjusted 3-year treatment effect of 0.29 D, which is statistically significant (P ¼ 0.004) but not clinically meaningful. A recent meta-analysis highlighted the effect size from various interventions using single vision lenses as a reference (Table 2).…”
Section: Discussionmentioning
confidence: 88%
“…54 Other studies found similar results with a small difference between PAL and conventional lenses. [55][56][57] Similarly, a more recent trial involving high-risk groups that is, children with high accommodative lags and near-point esophoria also failed to produce any significant benefits. 58 A more recent trial involving children with myopia randomised to wear single-vision spectacles or executive bifocals with þ 1.50 D add or þ 1.50 D add with 3D base in prism found that over a period of 24 months, myopia progression was on average À 1.55 D for those wearing single-vision spectacles, À 0.96 D for those with executive bifocals, and À 0.70 D for those with executive bifocals with base in prisms.…”
Section: Undercorrectionmentioning
confidence: 99%